Comparative Study of Marital Adjustment and Psychological Well-Being among Dual Career Couples - Sheetal Khatri; Sheetal Khatri *, Dr. Manju (International Journal of Indian Psychȯlogy, 2022)
A successful marriage not only indicates of a satisfied life but also generates a sense of well- being. Marriage is a union between two families and individuals. The present study was planned to understand the marital adjustment and psychological well-being among dual career couples. The sample of study involved 150 dual career couples (75 males and 75 females) of the state of Haryana with the age range of 30 to 45 years. The couples were administered marital adjustment questionnaire by Kumar and Rohatgi (1976) and psychological well-being scale by Philip H. Friedman (1994).